Transonic nacelle design for future medium range aero-engines - Schreiner, B. Deneys J.; MacManus, David G.; Tejero, Fernando; Sánchez-Moreno, Francisco; Sheaf, Christopher T. (International Council of the Aeronautical Sciences (ICAS), 2022)
It is expected that future civil aero-engines will operate at low specific thrust and high-bypass ratios to improve propulsive efficiency. This may result in an increment in fan diameter and associated weight and nacelle drag penalties. For this reason, these new architectures may use compact nacelles to meet the benefits of the new engine cycles. The aim of the current work is to evaluate the aerodynamic design and performance of compact nacelles for medium range, single-aisle aircraft with a cruise Mach number of M = 0.80. This work encompasses the 3D multi-point, multi-objective optimisation of nacelles by considering cruise conditions as well as a range of off-design requirements such as an increased cruise Mach number, a windmilling engineout diversion scenario and a windmilling end-of-runway case at high-incidence. This paper also explores the robustness and sensitivity of selected designs to flight Mach number (M), massflow capture ratio (MFCR) and angle of attack (AoA). The limits of the feasible design space for this new design challenge are identified. It is concluded that relative to a conventional aero-engine nacelle, the nacelle length (Lnac/rhi) can be reduced by approximately 13% with a mid-cruise drag reduction of 5.8%, whilst maintaining an acceptable aerodynamic performance at off-design conditions.
© The Author.
Keywords: nacelle; transonic; UHBPR; multi-objective optimisation